What factors influence firm perceptions of labour market constraints to growth in the MENA region?. Issue 8 (2nd November 2015) - Fakih, Ali; Ghazalian, Pascal L.
Abstract : Purpose: – Labour market constraints constitute prominent obstacles to firm development and economic growth of countries located in the Middle East and North Africa (MENA) region. The purpose of this paper is to examine the implications of firm characteristics, national locations, and sectoral associations for the perceptions of firms concerning two basic labour market constraints: labour regulations and labour skill shortages. Design/methodology/approach: – The empirical analysis is carried out using firm-level data set sourced from the World Bank's Enterprise Surveys database. A bivariate probit estimator is used to account for potential correlations between the errors in the two labour market constraints' equations. The authors implement overall estimations and comparative cross-country and cross-sector analyses, and use alternative estimation models. Findings: – The empirical results reveal some important implications of firm characteristics (e.g. firm size, labour compositions) for firm perceptions of labour regulations and labour skill shortages. They also delineate important cross-country and cross-sector variations. The authors also find significant heterogeneity in the factors' implications for the perceptions of firms belonging to different sectors and located in different MENA countries. Originality/value: – Reforms in labour regulations and investment in human capital are important governmental policy interventions for promoting firm development and economic growth in the MENA region. This paper contributes to the empirical literature by analysing the factors influencing the perceptions of firms located in the MENA region concerning labour regulations and labour skill shortages. It provides policy-makers with information needed in the design of labour policies that attenuate the impacts of labour market constraints and enhance the performance of firms and the long-run economic growth.